Pengaruh Intensitas Bermain Game Online Simulasi terhadap Perkembangan Keterampilan Sosial pada Remaja - Vergio Gary; Untung Subroto (YASIN, 2026)
Social skills are a crucial aspect of adolescent development and are presumed to be associated with the intensity of playing simulation games. This study aimed to determine the effect of simulation game playing intensity on adolescents’ social skills. The participants were 242 adolescents aged 12–21 years who actively played simulation games such as Roblox, The Sims, and Minecraft (roleplay/simulation modes). The study employed a quantitative method with simple linear regression analysis. The results showed that the intensity of playing simulation games had a significant effect on adolescents’ social skills (p = 0.000). The coefficient of determination of 0.518 indicated that simulation game playing intensity contributed 51.8% to adolescents’ social skills, meaning that more than half of the variance in social skills could be explained by simulation game playing intensity, while the remaining 48.2% was influenced by other factors beyond the scope of this study. In addition, the correlation obtained was strong and positive (r = 0.601), indicating that the higher the intensity of playing simulation games, the higher the adolescents’ social skills. These findings affirm a meaningful relationship between simulation game playing intensity and adolescents’ social skills and suggest that patterns of simulation game play need to be taken into account when understanding the dynamics of social skills development in this age group.